Impacts of Sediments on Coral Energetics: Partitioning the Effects of Turbidity and Settling Particles - Junjie, R.; Browne, Nicola; Erftemeijer, P.; Todd, P. (PLOS, 2014)
Sediment loads have long been known to be deleterious to corals, but the effects of turbidity and settling particles have not previously been partitioned. This study provides a novel approach using inert silicon carbide powder to partition and quantify the mechanical effects of sediment settling versus reduced light under a chronically high sedimentary regime on two turbid water corals commonly found in Singapore (Galaxea fascicularis and Goniopora somaliensis). Coral fragmentswere evenly distributed among three treatments: an open control (30% ambient PAR), a shaded control (15% ambient PAR) and sediment treatment (15% ambient PAR; 26.4 mg cm22 day21). The rate of photosynthesis and respiration, and the dark-adapted quantum yield were measured once a week for four weeks. By week four, the photosynthesis to respiration ratio (P/R ratio) and the photosynthetic yield (Fv/Fm) had fallen by 14% and 3–17% respectively in the shaded control,contrasting with corals exposed to sediments whose P/R ratio and yield had declined by 21% and 18–34% respectively. The differences in rates between the shaded control and the sediment treatment were attributed to the mechanical effects of sediment deposition. The physiological response to sediment stress differed between species with G. fascicularis experiencing a greater decline in the net photosynthetic yield (13%) than G. somaliensis (9.5%), but a smaller increase in the respiration rates (G. fascicularis = 9.9%, G. somaliensis = 14.2%). These different physiological responses were attributed, in part, to coral morphology and highlighted key physiological processes that drive species distribution along high to low turbidity and depositional gradients.